The Effect of Online Learning on Student Learning Interest and Motivation - Mispandi Mispandi; Agus Riswanto; Ilfa Ilfa (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2022)
Abstract: The purpose of this study was to determine the effect of online learning on the interest and learning motivation of Hamzanwadi University economics students. The type of research is quantitative research using simple random sampling technique, and the data collection technique is a Google form questionnaire using a Liker scale, namely strongly agree 3, agree 2, and disagree 1. The data analysis technique uses simple linear regression analysis. Then the results of the study show that online learning on learning interest is obtained tcount 7.697 > tÂ table 1.989, at a significant level of 5%. The magnitude of the influence of online learning on learning interest based on the results of the hypothesis test is 42.9% while the remaining 57.1% is influenced by other factors not examined. While the results of data analysis on online learning variables on learning motivation obtained tcount 5.156 > ttable 1.989, at a significant level of 5%. The magnitude of the influence of online learning on learning interest based on the results of the hypothesis test is 25.2% while the remaining 74.8% is influenced by other factors not examined.Keywords: Online Learning, Learning Interest and Learning Motivation Â Abstrak: Tujuan dari penelitian ini adalah untuk mengetahui pengaruh Pembelajaran Daring terhadap Minat Dan Motivasi Belajar Mahasiswa Pendidikan Ekonomi Universitas Hamzanwadi. Jenis penelitian yaitu penelitian kuantitatif dengan teknik simple random sampling, dan teknik pengumpulan data yaitu angket google form menggunakan skala liker yakni sangat setuju 3, setuju 2, dan tidak setuju 1. Teknik analisis data menggunakan analisis regresi linier sederhana. Maka hasil penelitian menunjukkan bahwa pembelajaran daring terhadap minat belajar diperoleh thitung 7,697 > tÂ tabel 1,989, pada taraf signifikan 5%. Adapun besarnya pengaruh pembelajaran daring terhadap minat belajar berdasarkan hasil uji hipotesis 42,9% sedangkan sisanya yakni 57,1% dipengaruhi oleh faktor lain yang tidak diteliti. Sedangkan hasil analisis data variabel pembelajaran daring terhadap motivasi belajar diperoleh thitung 5,156 > ttabel 1.989, pada taraf signifikan 5%. Adapun besarnya pengaruh pembelajaran daring terhadap minat belajar berdasarkan hasil uji hipotesis 25,2% sedangkan sisanya yakni 74,8% dipengaruhi oleh faktor lain yang tidak diteliti.Kata Kunci: Pembelajaran Daring, Minat Belajar dan Motivasi Belajar